1992
DOI: 10.1002/1097-0142(19920401)69:7<1651::aid-cncr2820690703>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there patients with stage i rectal carcinoma at risk for failure after abdominoperineal resection?

Abstract: The clinical courses of 64 patients undergoing abdominoperineal resection for Stage I lower rectal carcinoma (tumors confined to the muscularis propria without lymph node involvement) were reviewed to identify subsets at risk for failure. Twelve of 12 patients with tumors limited to the submucosa remained disease free without evidence of recurrence. Of the 52 patients with muscularis propria involvement, there have been eight failures with three patients having local failure only, three patients with local fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Studies of CRC have reported recurrence rates between 0 and 16% for patients with stage I disease. [11][12][13][14][15][16][17][18][19][20][21] This can possibly be explained by differences in surgical technique, follow-up times, retrospective design and the small sample size of most studies. In our series, even patients with the most favourable pathological features (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of CRC have reported recurrence rates between 0 and 16% for patients with stage I disease. [11][12][13][14][15][16][17][18][19][20][21] This can possibly be explained by differences in surgical technique, follow-up times, retrospective design and the small sample size of most studies. In our series, even patients with the most favourable pathological features (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…T2 stage tumor [8-10], lymphovascular invasion [7, 8], lower rectal lesions [9], male sex [7], a poorly-differentiated carcinoma [7] and high preoperative carcinoembryonic antigen value [10] were identified as influential factors related to the recurrence of stage I colorectal cancer in previous studies. Table 5 summarizes the results of previous studies related to the recurrence of first-stage colorectal cancer and compares them with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Local recurrence of pT1 tumors after abdominoperineal resection is low (0-10 percent) with a 0 percent local recurrence rate reported in some series. 17,18 Overall five-year survival rates for pT1 rectal cancers radically excised range from 78 to 100 percent. Local recurrence rates after conventional transanal excision without chemoradiation range from 0 to 33 percent for pT1 disease.…”
Section: Discussionmentioning
confidence: 99%